ICT knowledge transfer for development in the non-formal education: a case of jua kali sector in Kenya. - Momanyi, Christopher; Omwenga, Vincent Dr. (Strathmore University, 2021)
One of the millennium development goals is the attainment of Education For All (EFA).Attainment of Education For All means inclusion of those in the informal sector in the skill training programmes. Large gaps in skill training exist in the informal sector which is commonly known as Jua Kali sector, knowledge transfer can bridge these gaps. Training highly skilled manpower for economic development is a challenge. The formal education system has not addressed this challenge. Development cannot be achieved without knowledge transfer; training in skills will entail training skills that can be transferred to other areas through knowledge transfer. Vocationalisation of education as means of improving skills development in the informal sector seem to have failed as the Vocational Training Institutions set up by the government are seen to be institutions for failures, there is more emphasis on certificates rather than on practical skills. Thus leaving those in the informal sector to acquire skills through apprenticeship. Not all vocational institutions teach ICT skills due to the exorbitant costs. A group of 60 Jua Kali artisans was selected from a group of artisans who had undergone ICT and Business skills training, a comparison was done with another 60 artisan from the same are using a Z test statistic. From the data obtained it was proved that the trained artisans were far better than those not trained. Another analysis was dome on knowledge transfer; it was found that the trained artisans had acquired other skills they were not directly taught during the training.